2005
DOI: 10.3171/jns.2005.103.1.0038
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransplantation for patients with subcortical motor stroke: a Phase 2 randomized trial

Abstract: Human neuronal cells can be produced in culture and implanted stereotactically into the brains of patients with motor deficits due to stroke. Although a measurable improvement was noted in some patients and this translated into improved activities of daily living in some patients as well, this study did not find evidence of a significant benefit in motor function as determined by the primary outcome measure. This experimental trial indicates the safety and feasibility of neuron transplantation for patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
297
2
14

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 415 publications
(317 citation statements)
references
References 29 publications
4
297
2
14
Order By: Relevance
“…Два последовательных клинических ис-пытания продемонстрировали возможность стереотаксического введения культивируе-мых нейральных стволовых клеток [28,29]. В первом исследовании авторы провели им-плантацию 2-6 млн клеток непосредственно в зону повреждения 12 больным с хронически-ми инфарктами в области базальных ганглиев [28].…”
Section: нейральные прогениторные клетки и дру-гие стволовые клетки дunclassified
See 1 more Smart Citation
“…Два последовательных клинических ис-пытания продемонстрировали возможность стереотаксического введения культивируе-мых нейральных стволовых клеток [28,29]. В первом исследовании авторы провели им-плантацию 2-6 млн клеток непосредственно в зону повреждения 12 больным с хронически-ми инфарктами в области базальных ганглиев [28].…”
Section: нейральные прогениторные клетки и дру-гие стволовые клетки дunclassified
“…Впоследствии теми же исследователями была проведена вторая фаза рандомизирован-ного слепого исследования на 18 пациентах: 9 пациентов с ишемическим инсультом и 9 па-циентов с геморрагическим инсультом [29].…”
Section: нейральные прогениторные клетки и дру-гие стволовые клетки дunclassified
“…Interestingly, they reported the negative effect due to comorbidities [34]. The second one was performed using human neuronal cells and report the safety and feasibility of neuron transplantation for patients with motor stroke [35]. Other clinical trials using bone marrow derived stem cell (BMSC) in stroke have shown the feasibility and safety of the approach [36][37][38][39].…”
Section: Neural Progenitor Cell Therapy In the Post-acute Phase Of Stmentioning
confidence: 99%
“…There is considerable biological doubt, however, regarding the plausibility of modifying disability via cell engraftment, as noted above, and the justification for studying this group of patients has initially been based on stable neurological deficits offering a suitable environment for detection of any adverse effects. Older trials in this setting have used modified teratocarcinoma derived cells 41,42 or porcine xenografts, 43 neither cell type being developed further. The protocols from these older studies have formed the template for recent trials of direct intracerebral delivery.…”
Section: Late Subacute or Chronic Strokementioning
confidence: 99%